المحبة والعشق عند إخوان الصفا - قصير، حيدر عبدالحسين (جامعة البصرة - كلية الآداب, 2016)
تعتبر المحبة والعشق من الناحية الفلسفية علة وجود العالم وحركته وكماله، ثم هي عند إخوان الصفاء حالة مرضية تحدث نتيجة للمغالات الشديدة في الحب مما ينعكس ذلك بآثار سلبية على شخصية العاشق سواء من الناحية النفسية أو البدنية. وقد حدد الإخوان تبعا لذلك أنواع النفوس ومعشوقاتها ومحاولتهم ربطها بموجبات أحكام النجوم باعتبارها العلة والسبب في توليد المحبة والعشق، ناهيك عن الاهتمام بالأخلاق كسلوك فردي وجماعي في سبيل ترقي الإنسان الي المراتب العليا مع إبراز دور المعرفة الصوفية لأجل تنبيه النفس من نومة الغفلة ورقدة الجهالة.
From the philosophical point of view, love is the cause of the existence and perfection of the world. However, for the brethern of Purity, it is a morbid state that results from exageration in love, which is reflected negaticely on the lover’s bodily and spiritual state. They divided types of souls and their adoration, and related them to the lovement of the stars, since the stars are the cause behind adoration. They also took interest in ethics on a personal and collective levels, and it is responsible for honing human behaviour to higher degrees, as well as their interest in the revelation and Sufi knowledge in awakening the soul
Keywords: المحبة -- العشق -- الفكر الفلسفي -- إخوان الصفا -- الفلسفة الإسلامية